Climate change and human rights With reference to the regions of southern Iraq - Prof.Dr.Kareem Saied Kenbar (The college of law and political science journal, 2023)
The study of the relationship between climate change and the resulting various environmental problems and disasters and between basic human rights, foremost of which is the right to live in a safe and clean environment, is of great importance by human rights bodies and institutions and by many researchers in humanitarian and scientific disciplines as well.This is because the changes taking place in the natural environment of man, especially those related to global warming, the escalation of pollution rates, water scarcity, the shrinking of green spaces, the spread of drought, the expansion of desertification and the spread of epidemics, affect, either directly or indirectly, human rights in his life, security, stability, livelihood and health, and it is a sufficient justification to study this The issue, which has become, in fact, a humanitarian problem that is not limited to a particular society, but rather includes almost all human societies, as it warns of the outbreak of internal and internal disputes and conflicts, whose features have begun to appear in more than one geographical area.Hence, the main objective of this research is to study climate change and its impact on human rights, especially the right to live in a safe and clean environment in accordance with the regulations approved by international conventions.To achieve this, the research relied on the propositions of the analytical descriptive approach in dealing with the phenomenon, the subject of the research, which was divided in addition to the introduction and conclusion into three sections:The first section examines the theoretical framework for the concept of climate change and the concept of human rightsThe second topic deals with the impact of climate change on human rightsThe third topic deals with the effects of environmental pollution on human rights in the regions of southern Iraq.